The Location and Accessibility of the Second Mesiobuccal Canal in Maxillary First Molar - Tuncer, Aysun Kara; Haznedaroglu, Faruk; Sert, Semih (European Journal of Dentistry, 2010)
Objective:The purpose of this study was to examine the location and accessibility of the second mesibuccal canal in maxillary first molar of a Turkish sub-population.Methods: Presence and accessibility of the MB2 canal in 110 extracted maxillary first molars was examined with unaided vision, dental loups and the DOM. To characterize the geometrical location of MB2 canals, photographs of pulp chambers were obtained.Results: With the unaided vision, 58 MB2 canal orifices and after evaluation with the dental loup, DOM an additional 28 MB2 canal orifices were detected. In 65 molars, the MB2 canal orifices was located 0.87 mm distally and 1.73 mm palatally to the main mesiobuccal canal and in the remaining 21 molars was 0.72 mm mesially and 1.86 mm palatally.Conclusion: Presence of second mesiobuccal canal was similar to the other studies but in a Turkish sub-population it originates mainly distal to the main MB canal. (Eur J Dent 2010;4:12-16)
Keywords: Second mesiobuccal canal; Maxillary molar; Location; Accessibility